Water resource management in Central Asia: a Japanese attempt to promote water resource efficiency. Issue Volume 15:Issues 1(2016) (2nd January 2016) - Dadabaev, Timur
ABSTRACT: This paper examines one instance of a capacity-building attempt by Japan to reduce water demand and increase the efficiency of scarce water resource use in Central Asia. Focusing on Japanese involvement in Uzbekistan, this paper demonstrates how Japan attempted to define priority areas, assistance principles and approaches to address this issue. Through its involvement, Japan attempted to place a great degree of trust and confidence in this region. The outcomes of these efforts to create water demand reduction and management schemes have been only partially successful. The Japanese "Integrated Water Resources Management" (IWRM) proposal met with limited success because of its various logistical and conceptual weaknesses. However, the demand for a water reduction agenda and the efficient consumption of water were well received by all participants and stakeholders.